LA CULTURA INDÍGENA FRENTE AL PROYECTO HIDROELÉCTRICO DE BORUCA: TESTIMONIO - Coto Martén, Fernando (2023)
The Boruca Hydro Electric Proyect is being balancede, with estrategic character and the involvement of de participating institucions and people. The benefit obtained by the iniciative of ICE (The Costa Rica Electric Company) is taken in to acount also costs that will be generated with competion the proyect will be analized; the negociation process, the social impact and also respect given to the criterion of the native people. The opcion for development with a focus on solidarity, with the perspective of the cultural, territorial and health rights is being put foward.